Internal strain assessment using FBGs in a thermoplastic composite subjected to quasi-static indentation and low-velocity impact. (1st May 2019) - Mulle, M.; Yudhanto, A.; Lubineau, G.; Yaldiz, R.; Schijve, W.; Verghese, N.
Abstract: We present, for the first time, an experimental investigation of internal strain monitoring in thermoplastic composites subjected to quasi-static indentation and low-velocity impact using embedded fiber Bragg gratings (FBGs). The goal is to highlight the interest and limitations of the in-core instrumentation of glass fiber-reinforced polypropylene laminates subjected to these two classical loading conditions. We propose an instrumentation strategy utilizing FBGs that is expected to provide a reliable set of internal strain values and strain rates, which can be used for the analysis of the damage behavior and the validation of a numerical mesoscale model of laminates. Based on a specific sensor insertion procedure, monitoring techniques and optical observations, we show how the applied methodology alleviates major issues, such as determining the in-plane and through-thickness position of the embedded FBGs, their influence on the structural integrity or the interpretation of the reflected optical signal.